Anomalous High Bifurcation of the Common Femoral Artery at the Groin: Management of Gsv Incompetence with Endovenous Laser Ablation. (August 2013) - Lekich, C; Campbell, W; Walton, S; Hannah, P
Objectives: To discuss safety of EVLA in anomalies of the GSV anatomy. To review and discuss complications of surgery involving anomalous anatomy. Method: We report a case of high bifurcation of the common femoral artery wrapping around the saphenofemoral junction. Results: Successful ablation was achieved with no adverse consequences. Conclusion: EVLA is a safe treatment for SFJ/GSV incompetence in the presence of vascular anomalies that have historically resulted in serious vascular complications from surgery.